Hubungan Pola Asuh Orang Tua dengan Tingkat Kematangan Emosi Siswa - Dola Desvita; Linda Fitria; Rini Sefriani (Universitas Putra Indonesia YPTK Padang, 2022)
Emotional maturity is a condition where a person is able to control, control and channel his emotions based on the situation and conditions that occur, so that he has a good level of emotional stability in solving a problem that occurs. The factors that can affect emotional maturity here are one of them influenced by parenting patterns, where parenting here is how to educate, maintain, nurture and guide their children towards the maturation process. The purpose of this study was to determine the relationship between parenting patterns with the level of emotional maturity of students. This study examines the relationship between parenting patterns with the level of emotional maturity of students, where the method used in this study is quantitative correlation. The population in this study amounted to 210 people who were registered with a sample of 138 students. The sampling technique used is purposive sampling. The instrument in this study was a questionnaire with a likert scale. Data analysis was performed using statistical programs on IBM Statistical 20 computers and Microsoft Excel. Based on the results of data processing, the rcount value is 0.450 with an rtable value of 0.165, the rcount value is greater than the rtable value 0.450> 0.1656, it can be concluded that there is a positive and significant relationship between the relationship between parenting patterns and the level of emotional maturity of students.